2017
DOI: 10.1016/j.rboe.2016.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous bilateral patellar tendon rupture

Abstract: Bilateral patellar tendon rupture is a rare entity, often associated with systemic diseases and patellar tendinopathy. The authors report a rare case of a 34-year-old man with simultaneous bilateral rupture of the patellar tendon caused by minor trauma. The patient is a retired basketball player with no past complaints of chronic knee pain and a history of steroid use. Surgical management consisted in primary end-to-end tendon repair protected temporarily with cerclage wiring, followed by a short immobilizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
(11 reference statements)
0
5
0
2
Order By: Relevance
“…We found that patients with bilateral ruptures can expect to return to their normal baseline mobility, including a return to sports by 6–12 months post-operatively. Three patients had returned to their baseline level of mobility by six months post procedure [2] , [4] , [7] . Only one patient had a documented post-operative complication, with Taylor et al's patient developing a pulmonary embolism on post operative day 1, however they were successfully treated with heparin [5] .…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…We found that patients with bilateral ruptures can expect to return to their normal baseline mobility, including a return to sports by 6–12 months post-operatively. Three patients had returned to their baseline level of mobility by six months post procedure [2] , [4] , [7] . Only one patient had a documented post-operative complication, with Taylor et al's patient developing a pulmonary embolism on post operative day 1, however they were successfully treated with heparin [5] .…”
Section: Discussionmentioning
confidence: 95%
“…We limited our search to full text, English language publications for adult patients. We excluded studies in patients with risk factors present for tendon rupture, which yielded 17 suitable case reports ( Table 1 ) [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] . Of note, there were three paediatric cases in the literature, one of which had a known diagnosis of Ehlers-Danlos syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported in SLE [3], rheumatoid arthritis [5], chronic renal failure [6], and primary hyperparathyroidism [7]. Moreover, cases have been reported in apparently healthy people [8], and during sports activities [9]. Treatments like CS [10], FQ [11] and statins [12] also predispose to BPTR.…”
Section: Discussionmentioning
confidence: 99%